Critical reading and writing across the curriculum assisted By Metacognitive Strategy (BTS) toward student study club at Undiksha - Yasa, I Nyoman; Suyitno, Imam; Pratiwi, Yuni (citeus, 2016)
This paper aims at explaining the implementation of RAWAC (Reading and Writing across Curriculum) in teaching essay for college students. Using an action research based integrated with hermeneutic technique, this study was conducted in Kelompok Belajar Mahasiswa (Student Study Club) at Ganesha University of Education, Bali. The result of the study indicates that this model is able to synchronize the excellent aspects of reading-writing and metacognition as those give benefits to the students in terms of strengthening their critical thinking in exploring ideas, their discipline attitude during the process of planning, monitoring, and evaluating concepts, and also strengthening the students’ self-regulated learning in writing essay. Implementing RAWAC improve the students’ ability in writing essays, especially in exploring ideas, organizing the writing, choosing the diction and enhancing their writing technique.